A philosophy of lying - Svendsen, Lars Fr. H., 1970- (Reaktion Books, 2022)
"This book is a comprehensive investigation of lying in everyday life. What exactly is a lie, and how does lying differ from related phenomena such as 'bullshit' or being truthful? Lars Svendsen also investigates the ethics of lying -- why is lying almost always morally wrong, and why is lying to one's friends especially bad? The book concludes by looking at lying in politics, from Plato's theory of the 'noble lie' to Donald Trump. Svendsen's conclusion is that, even though we all occasionally lie, we are for the most part trustworthy. Trusting others makes you vulnerable, and you will be duped from time to time, but that is -- all things considered -- preferable to living in a constant state of distrust."--